2023
DOI: 10.1021/acsomega.3c01241
|View full text |Cite
|
Sign up to set email alerts
|

Role of Race/Ethnicity, Sex, and Age in Surface-Enhanced Raman Spectroscopy- and Infrared Spectroscopy-Based Analysis of Artificial Colorants on Hair

Abstract: Forensic microscopy has been used in forensic hair analysis to determine the racial origin of hair samples. However, this technique is subjective and often inconclusive. Although, to a large extent, this problem can be solved with the use of DNA analysis, which is capable of identifying the genetic code, biological sex, and racial origin from a strand of hair, this PCR-based analysis of hair is time-and labor-consuming. Infrared (IR) spectroscopy and surface-enhanced Raman spectroscopy (SERS) are emerging anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This specific finding provided a hopeful perspective for pediatric AA cases, contrasting with the absence of correlation between other dermoscopic features and clinical signs, challenging the universally diagnostic utility of trichoscopy in AA. 6,9,10 The study's findings on the occurrence of broken hairs and empty follicular openings in children, while statistically insignificant, aligned with observations from other research focusing on AA in darker skinned patients, indicating potential racial or skin type differences in AA presentation. 11 The observed higher prevalence of pigtail hairs in adults, despite not being statistically significant, reflected the nuanced variability of AA across different age groups.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This specific finding provided a hopeful perspective for pediatric AA cases, contrasting with the absence of correlation between other dermoscopic features and clinical signs, challenging the universally diagnostic utility of trichoscopy in AA. 6,9,10 The study's findings on the occurrence of broken hairs and empty follicular openings in children, while statistically insignificant, aligned with observations from other research focusing on AA in darker skinned patients, indicating potential racial or skin type differences in AA presentation. 11 The observed higher prevalence of pigtail hairs in adults, despite not being statistically significant, reflected the nuanced variability of AA across different age groups.…”
Section: Discussionsupporting
confidence: 81%
“…Considering a comparison test for the ratio in two independent samples with a significance level of 0.05, 80% power, and a one-to-one ratio with an expected ratio of 0.4 in the first group and 0.65 in the second group, following a study, 6 the minimum required sample size was determined to be 124.…”
Section: Sample Size Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported study by our group showed that SERS could be used to distinguish hair from different races/ethnicities, age groups, and sexes 15 . Therefore, the reported results should be valid only for young female individuals of Caucasian race.…”
Section: Methodsmentioning
confidence: 97%
“…RS has previously been used to identify urine, sweat, semen, blood, hair colorants, and gunshot residue [14][15][16][17][18][19]. It should be noted that RS is a non-destructive and non-invasive technique [20][21][22]. Therefore, it can be used to identify the origin of highly vulnerable historical fabrics that have dyes or pigments [9].…”
Section: Introductionmentioning
confidence: 99%